The physical progress of a professional Scottish soccer academy over a ten-year period - Craig, T. P.; Maughan, P.; McArdle, M. P.; Clark, D. R.; Reid, D. (Open Access Journal of Sports Medicine, 2024)
Background Increases in high-intensity locomotor activity of match play have been recorded in elite soccer. This places an onus on academy practitioners to develop players for the future demands of the game. At an academy level, locomotor data are not available for analysis over a longitudinal period, and thus changes can only be assessed with physical attribute assessment. The aim of the present study is to establish if changes in physical capacity were observed in a professional Scottish soccer academy over a ten-year period.